Use of the corneal topography for a better professional training in patients with pterigion surgery - Mildred Karelia Arias Domínguez; Nelson Milán González; María Aurelia Lazo Pérez; Damaris Fuentes Pelier (Centro Provincial de Información de Ciencias Médicas, 2021)
Introduction: Pterigium surgery is demanded as a skill in the first year of the residency and the topographical evaluation is a key element to evaluate corneal modifications and to improve clinical -surgical skill of training surgeons. Objective: To determine the corneal modifications in patients with pterigium surgery in the Ophthalmological Center from Santiago de Cuba, from January 2019 to the same month in 2021, in whom a topographical evaluation was carried out before and after the surgical procedure. Results: Female sex  (60.4 %), age group 40-49 (5.8 %), the disease grade II (43.4 %) and induced astigmatism as the most frequent complication (33.9 %) predominated. Average corneal power suffered a variation of 43.25 D and 45.75 and the topographical astismatism decreased from 4.75 to 3.55 D. Conclusions: With the use of topography it was proven that there are corneal modifications derived from pterigium invasion to the cornea and from the surgical manipulation.